A novel gas sensor based on porous α-Ni(OH)2 ultrathin nanosheet/reduced graphene oxide composites for room temperature detection of NOx. (29th March 2016) - Yang, Ying; Wang, Hongjie; Wang, Linlin; Ge, Yunlong; Kan, Kan; Shi, Keying; Chen, Junhong
Abstract : Porous α-Ni(OH)2 TNS/rGO composites have a sensitivity of 64.4% and a response time of 10.0 s to 97.0 ppm NO x . Abstract : A novel composite room temperature (RT) gas sensor based on a α-Ni(OH)2 thin nanosheet (TNS)/reduced graphene oxide composite (α-Ni(OH)2 TNS/rGO composites) was successfully synthesized via a facile reflux method. In this synthesis, Ni 2+ and urea were adsorbed on GO through electrostatic interactions in a water solution. The subsequent reflux treatment led to the transformation of the Ni(OH)2 TNS coated on GO and also to the reduction of graphene oxide. Compared to the pristine Ni(OH)2 TNS prepared in the absence of GO, the prepared α-Ni(OH)2 TNS/rGO composite showed higher NO x gas sensing performance with a low detection limit of 970 ppb, high response and fast response at RT. The enhanced sensing properties are attributed to the synergy of the superior conductivity of rGO and the 3D nanostructure of the α-Ni(OH)2 TNS/rGO composite. The present strategy for combining various hydroxide and nanoscaled building blocks into integrated 3D structures will open new opportunities for designing and synthesizing multifunctional composites.